Open Data-Driven 3D Building Models for Micro-Population Mapping in a Data-Limited Setting - Kittisak Maneepong; Ryota Yamanotera; Yuki Akiyama; Hiroyuki Miyazaki; Satoshi Miyazawa; Chiaki Mizutani Akiyama (Remote Sensing)
Urban planning and management increasingly depend on accurate building and population data. However, many regions lack sufficient resources to acquire and maintain these data, creating challenges in data availability. Our methodology integrates multiple data sources, including aerial imagery, Points of Interest (POIs), and digital elevation models, employing Light Gradient Boosting Machine (LightGBM) and Gradient Boosting Decision Tree (GBDT) to classify building uses and morphological filtration to estimate heights. This research contributes to bridging the gap between data needs and availability in resource-constrained urban environments, offering a scalable solution for global application in urban planning and population mapping.